Heritage in Narration: Reading a Contemporary Urban Fresco - Khelfallah, Sheherazad (El Omda in Linguistics and Discourse Analysis, 2024)
This article seeks to examine the layers of heritage inscribed in the urban fabric across the city’s landscapes, whose very presence sustains enduring memories, etymological traces, and cultic expressions. It is through the deciphering of a contemporary mural fresco in the city of Jijel that these stratified heritage narratives are interpreted, under the evocative forces of commemoration, roots, identity, tradition, dialect, and patron saints.